2019
DOI: 10.1016/j.aquaculture.2019.734326
|View full text |Cite
|
Sign up to set email alerts
|

Long term survival of cryopreserved mussel larvae (Mytilus galloprovinciallis)

Abstract: Due to the economic importance of the mussel Mytilus galloprovincialis in the Spanish aquaculture, there is a growing interest in developing alternative methods to ensure the supply of good-quality biological material and to minimize the uncertainty and variability that might be a source of economic risk for this sector. The aim of this work was to develop a successful cryopreservation 13 protocol for Mytilus galloprovincialis larvae and study long-term effects by assessing survival and 14 development post cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Improvements from our prior protocol for larvae were due to selection of the 72 h-old D-larval stage for cryopreservation, resulting not only in higher survival rates but also in increased quality of larval fitness. In addition, preference for the use of 72 h-old D-larvae is supported by our prior research that showed their higher tolerance to CPA toxicity and higher resistance to cryopreservation, compared with earlier development stages 35 , 41 . The optimized protocol produced close to 75% of normal D-larvae at day 2 of incubation, compared with only 25% success obtained with cryopreserved trochophores in a 48 h short-term post-thaw fitness evaluation 25 , 36 .…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…Improvements from our prior protocol for larvae were due to selection of the 72 h-old D-larval stage for cryopreservation, resulting not only in higher survival rates but also in increased quality of larval fitness. In addition, preference for the use of 72 h-old D-larvae is supported by our prior research that showed their higher tolerance to CPA toxicity and higher resistance to cryopreservation, compared with earlier development stages 35 , 41 . The optimized protocol produced close to 75% of normal D-larvae at day 2 of incubation, compared with only 25% success obtained with cryopreserved trochophores in a 48 h short-term post-thaw fitness evaluation 25 , 36 .…”
Section: Resultsmentioning
confidence: 61%
“…Selective breeding systems can be assisted by the application of cryopreservation tools, offering the possibility of storing interesting biological samples at high densities under minimal requirements compared to maintaining live stocks, able to survive and develop normally once they are thawed 20 , 22 , 38 . In addition to several advantages mentioned in the Introduction, the establishment of biobanks could be the way to overcome the logistical issues of obtaining and maintaining living shellfish broodstock, as well as lowering costs and effort 35 . For instance, shellfish hatchery requires daily a supply of diet composed of a mix of microalgal species in different proportions; continuous water flow and aeration are also needed, and the system must be efficient in terms of removing metabolites that can be deleterious.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transformative rearing technologies and husbandry regimes are integral to realizing the benefits of breeding programmes by ensuring optimal performances of the stocks. For example, cryopreservation of finfish milt (sperm) (Cabrita et al 2001;Yang et al 2018) and bivalve larvae (Suquet et al 2014;Rodriguez-Riveiro et al 2019) enables long-term storage of genetic material from optimal selection candidates. The high fecundity of aquatic species means that genetically improved stock can be disseminated from a single nucleus to a broad geographical and environmental range.…”
Section: Genomic Breeding Values (Gebv)mentioning
confidence: 99%
“…2014; Rodriguez‐Riveiro et al . 2019) enables long‐term storage of genetic material from optimal selection candidates. The high fecundity of aquatic species means that genetically improved stock can be disseminated from a single nucleus to a broad geographical and environmental range.…”
Section: Genetic Improvement Via Selective Breedingmentioning
confidence: 99%